Particularities in Urinary Tract Management before Pediatric Renal Transplantation in Small Children - Ascar, Priscila Cardoso Braz; Leão, Jovelino Quintino de Souza; Carvalho, Maria Fernanda Camargo de; Nogueira, Paulo Cesar Koch (Brazilian Journal of Transplantation, 2024)
The number of renal transplants in small children (infants or under 15 kg) has risen amid improved prenatal diagnosis, earlier referral to specialized centers, and advances in care of kidney failure patients. Most of these patients have congenital anomalies of the kidney and urinary tract, which need correcting prior to transplantation. In order to meet this challenge, the presence of a pediatric urologist working together with an experienced multidisciplinary team is paramount. This study provides a narrative review compiling details on the urological management of the urinary tract of low-weight patients with chronic kidney disease and congenital anomalies of kidney and urinary tract (CAKUT) referred for renal transplantation (RT). Objectives: Conduct a narrative review about urologic correction in small children before RT. Methods: Articles published in English language over a 20-year period were reviewed. The keywords considered for the research and article selection were pediatric RT or pediatric kidney transplantation and children or small children or small infants or young children or young infants and urinary tract reconstruction and CAKUT. Some articles that are reference to elucidate the urological aspects of the review were also included.